Existence of Religious Programmes in Analog Platform: A Case Study in Broadcast Media in West Java, Indonesia - Mahi M Hkikmat; Dadan Firdaus (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2021)
Religious programmes are important contents which should be inserted in all programmes in broadcast media. Although broadcasting platform can transform, but the religious programmes still exist. How are existences of the religious programmes in analog platform by the broadcast media? This query is described in a study by using interpretive-subjective approach with qualitative method to examine quantitative data via a case study discovered in broadcast media in West Java, Indonesia. Strategic considerations on urgency of religious programmes in broadcast media are normative mandate of laws which turn into basic characteristics of the citizens, and commitment idealism in carrying out the function of education, but the financial benefits are still lower.